Electroencephalogram, creatine kinase, and lactate dehydrogenase responses during preslaughter handling in goats handled by trained and untrained handlers - Kumar, P.; Abubakar, A. A.; Adewale, M. A.; Hayat, M. N.; Adamu, G.; Ajat, M.; Goh, Y-M.; Kaka, U.; Sazili, A. Q. (Journal of the Indonesian Tropical Animal Agriculture, 2024)
The present study evaluated the effect of training to livestock handlers on electroencephalogram (EEG) and plasma enzymes levels during preslaughter handling in goats. Six handlers were divided into three groups viz., trained (T-trained in basic animal handling practices, animal behavior, and animal welfare principles), contact trained (CT-not trained directly but interacted and saw the working of trained handlers), and untrained (UT-no formal training). Eighteen Boer cross bucks were used in the study by following a cross-over design and electroencephalogram spectrum, creatine kinase (CK), and lactate dehydrogenase (LDH) concentrations were recorded before handling (in lairage) and after handling (at slaughter point). The training of livestock handlers had a significant (p<0.05) effect on the total power (Ptot) and median frequency (MF) of the EEG spectrum. Whereas no significant (p>0.05) change was recorded in the alpha, beta, delta, theta, and gamma bands activity. The goats handled by trained handlers exhibited significantly (p<0.05) lower CK and LDH concentrations than goats handled by CT and UT handlers, thereby indicating higher preslaughter stress in goats handled by CT and UT groups. Therefore, the current study emphasizes the significance of providing training to livestock handlers in order to mitigate preslaughter stress levels in goats.